The dragon of Boeotia - Evslin, Bernard (New York : Chelsea House, 1987)
A fierce dragon plaguing a region of Greece comes into combat with the young prince, Cadmus of Phoenicia. The book's illustrations are famous works of art covering many centuries.
Keywords: Dragons -- Juvenile literature; Cadmus (Greek mythology) -- Juvenile literature; Mythology, Greek -- Juvenile literature